(untitled) (Research, Society and Development, 2024)
Dental veneers are an increasingly common type of procedure in dental offices due to patients’ growing search for clear, aligned smiles. The present work aimed to map the main materials and techniques used by dental surgeons to create veneers. An online questionnaire with objective questions was used on a sample of 103 participants from various locations in Brazil. Of these, 80.6% chose composite resin as the material most used by them. Regarding preparations prior to making the veneers, 72.8% responded that it depends on the case and the material to be used, while 21.4% said they always prepare the teeth and 5.8% reported not carrying out preparations. Regarding the mastery of the technique, 58.3% of respondents said they mastered the composite resin technique more, while 14.6% said they mastered the ceramic technique better and 27.2% said they mastered both techniques equally. 55.3% of respondents stated that the quality and quantity of dental remnants is the main factor when choosing the material to be used. This work demonstrated that the majority of dentists interviewed use composite resin to create veneers, as they believe it is the technique they most master.